Solid magnetoliposomes containing CaxMg1-xFe2O4 mixed ferrite nanoparticles - Cardoso, Beatriz D. (2019)
In this work, magnetoliposomes based on superparamagnetic nanoparticles, highly promising therapeutic nanosystems for cancer therapy, were developed. The polyphenolic antitumor compound curcumin was incorporated into the lipid bilayer of the developed magnetoliposomes, considering its strong hydrophobic character, which has been a barrier to its applicability in therapeutic applications. Therefore, the magnetoliposomes were evaluated as successful nanocarriers for curcumin to enhance its therapeutic potential in oncological therapy approaches.